ANALISIS PENGUKURAN KINERJA ORGANISASI DENGAN METODE BALANCED SCORECARD ( Pada KSU Karyawan Pemerintah Kota Semarang ) - Syamsiyah Syamsiyah; Naili Farida; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2013)
The research of goal was to determine the performance measurement in financial perspective, customer perspective, internal business perspective the process, learning and growth perspective of the balanced scorecard method at KSU Government Employee of Semarang city. This research is a qualitative descriptive analysis of financial and non-financial. Source of data used are primary data with a a questionnaire for customer satisfaction and employee mengetehui and indept interview to determine the valuation of the actualization of the vision, mission, goals, targets and strategies in setting weights on key performance indicator (KPI) as a performance assessment. Secondary data from the financial statements of a cooperative in 2010-2012. The results showed the performance of the cooperative is in a healthy position for the score obtained by the four perspectives. Conclusion that the balanced scorecard can be used as a method of measuring the performance of the cooperative is more comprehensive with not ignore the non-financial aspects that become the driving force for the progress of the cooperative. Suggestion that the management needs to maintain performance and improve the already good performance is still low in order to achieve the welfare of members. Planned cash inflows and cash out with maintaining liquidity ratio in improving the profitability ratio in order to increase the capital of cooperatives, especially in improving business.